ADDITIONAL BENEFITS OF ANTIHYPERTENSIVE MOXONIDINE THERAPY IN POSTMENOPAUSAL WOMEN WITH ARTERIAL HYPERTENSION - E. N. Dudinskaya; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To assess the effects of moxonidine in terms of target blood pressure (BP) achievement; to identify potential additional benefits of moxonidine and its effects on bone metabolism and bone mineral density (BMD) in postmenopausal women with arterial hypertension (AH).Material and methods. The study included 48 postmenopausal women with Stage 1-2 AH, aged 57-71 years.Results. All participants were divided into two groups by the type of antihypertensive therapy: those receiving moxonidine and those receiving angiotensin-converting enzyme inhibitors / angiotensin receptor antagonists (ACEI/ARA). All women also received calcium and vitamin D. All participants had AH and osteopenia (both in the lumbar spine and proximal femur, according to the X-ray absorptiometry results). In the moxonidine group, BP levels remained within the target range 48 weeks later. There was a significant reduction in the levels of a bone resorption marker (p=0,041), while the dynamics of an osteopoetic marker was statistically non-significant (p=0,31). A tendency towards increasing BMD in lumbar spine and proximal femur was also observed (p=0,059 and p=0,068, respectively). In the ACEI/ARA group, BP levels also remained within the target range 48 weeks later. However, no significant changes in the levels of bone metabolism markers were registered. There was a tendency towards decreasing BMD in lumbar spine and proximal femur (p=0,052 and p=0,054, respectively).Conclusion. Moxonidine therapy was associated with a significant reduction in bone resorption activity, as demonstrated by the decrease in the concentration of a bone resorption marker, as well as with a tendency towards increasing BMD.